Participer à la nouvelle Afrique du Sud ? - Sophie Chevalier (Ateliers d'Anthropologie)
The author of this article has spent several years in Durban (South Africa) researching the consumption practices of middle classes, as well as the commercial spaces in which these take place. Since their introduction, shopping malls have played a part in a political and ideological dimension, first during the apartheid period (when they helped intensify segregation), and today, as sites that testify to the emancipation of the non-white middle classes, and to the new South Africa. In this article, a historical anthropology of shopping malls, their introduction and their integration into the urban, social and racial fabric is combined with an ethnography of shopping itineraries, which show to what extent shopping malls are good for thinking about the historical transformations underway in this society.